2009
DOI: 10.1111/j.1365-2249.2009.04053.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiles for the human pancreas and purified islets in Type 1 diabetes: new findings at clinical onset and in long-standing diabetes

Abstract: SummaryType 1 diabetes (T1D) is caused by the selective destruction of the insulinproducing b cells of the pancreas by an autoimmune response. Due to ethical and practical difficulties, the features of the destructive process are known from a small number of observations, and transcriptomic data are remarkably missing. Here we report whole genome transcript analysis validated by quantitative reverse transcription-polymerase chain reaction (qRT-PCR) and correlated with immunohistological observations for four T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
74
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 51 publications
(54 reference statements)
8
74
1
Order By: Relevance
“…This finding is in accordance with available whole-genome profiling data that show TMEM27 as one of the 370 genes differentially expressed between diabetic and control human islets [26]. In the same line, a recent report shows that TMEM27 expression is tenfold lower in islets from recent diagnosed type 1 diabetic pancreatic donors as compared with healthy controls [27]. Taken together, these data point to TMEM27 as a potentially important protein for consideration in beta cell physiology and diabetes in humans.…”
Section: Tmem27 Rolesupporting
confidence: 79%
“…This finding is in accordance with available whole-genome profiling data that show TMEM27 as one of the 370 genes differentially expressed between diabetic and control human islets [26]. In the same line, a recent report shows that TMEM27 expression is tenfold lower in islets from recent diagnosed type 1 diabetic pancreatic donors as compared with healthy controls [27]. Taken together, these data point to TMEM27 as a potentially important protein for consideration in beta cell physiology and diabetes in humans.…”
Section: Tmem27 Rolesupporting
confidence: 79%
“…7C), characteristic for viral infection, and is similarly detected in pancreata and islets from patients at clinical onset and long-standing diabetes (12). Furthermore, the gene-expression program induced by enteroviral infection of human islets (14,15) is also prominently mimicked by the IKK2-CA Pdx-1 model, suggesting that IKK/NF-kB is a critical downstream effector in this context.…”
Section: Discussionmentioning
confidence: 79%
“…3I). This inflammatory profile is reminiscent of those found in islets from patients, in animals with type 1 diabetes (11,12), and in normal human islets subjected to cytokines or enteroviruses (13)(14)(15).…”
Section: Ikk2-ca-induced Diabetes Is Associated With Inflammation Andmentioning
confidence: 84%
“…Autoreactive T cells were identified in vitro by expansion against insulin, GAD, I-A2, IGRP (7)(8)(9)(10), and ex vivo by positive staining with self-peptide-MHC tetramers (11,12). Although there are no data on the specificity of intrapancreatic T cells in human T1D, phenotypic analysis of infiltrating lymphocytes have shown that the human pancreas is infiltrated with both CD8 + and CD4 + T cells (13)(14)(15)(16)(17)(18). In addition, several analyses of the TCR repertoire of pancreatic T cells demonstrate the dominance of some Vb families, despite the lack of consensus imposed by the interindividual variability of MHC (15,16,19,20).…”
Section: T Ype 1 Diabetes (T1d) Is An Autoimmune Disease Defined By Tmentioning
confidence: 99%